A New Limonoid from the Seeds of Chisocheton lasiocarpus (Meliaceae) - Ronauli Fitriana; Nurlelasari Nurlelasari; Darwati Darwati; Desi Harneti; Tri Mayanti; Rani Maharani; Unang Supratman (UNIVERSITAS SEBELAS MARET (UNS), 2021)
A New Limonoid from the Seeds of Chisocheton lasiocarpus (Meliaceae). Chisocheton is one of Meliaceae genus, which has about 53 species spreading in subtropical and tropical regions. One of the species is Chisocheton lasiocarpus. Chisocheton is rich in limonoids that have various biological activities such as anticancer, antimalarial, anti-inflammatory, antifeedant, antiviral, neuroprotective, and antimicrobial properties. This study aims to isolate limonoids from the seeds of C. lasiocarpus, and determine the structures. The dry powder of seeds of C. lasiocarpus (203.75 g) was macerated with subsequent n-hexane, ethyl acetate, and methanol. Extract of ethyl acetate was separated and purified using chromatography methods until a new limonoid, lasiocarpines (1) and one known limonoid, 14β,15β-epoxynimonol (2) were obtained. The purification process was guided by Ehrlich reagent. The chemical structures were identified by UV, IR, 1H-NMR, 13C-NMR, 2D NMR, and mass spectrometry.